A survey on scientific authenticity of health information in Iranian popular magazines: A case study - Ourfa Hovsepyan; Firoozeh Zare_Farashbandi; Gholamreza Askari; Akbar Hassanzadeh (Wolters Kluwer Medknow Publications, 2018)
Background: The content of the mass media is a suitable tool for making changes to the society. One of the most read news in the mass media is nutritional information. The goal of this study is to assess the scientific authenticity of such information published in Iranian popular magazines. Materials and Methods: This study is a qualitative study (content analysis) and uses bibliographic approach. A researcher-designed checklist is used as data gathering tool, and the statistical population included the messages obtained from the printed material in 173 volumes of 8 Iranian popular magazines. 10 most frequent messages were identified, and their scientific authenticity was investigated using Pubmed and IranMedex databases. The SPSS Software version 24 (IBM Corporation, Armonk, New York, USA) was applied in the analysis of this work. Results: The findings indicated that preventive trends had the highest (86.8%) and the treatments had the lowest (4.2%) frequency. Concerning the type of cancer, more than half (51.2%) of the conclusions were about cancer. Regarding authorship, 68% of articles were author signed, but the profession of 66.4% of the authors was not clear. Regarding references, only 25.4% of the articles had validated references. Conclusion: It is revealed that 70% of the "nutrition information" related to cancer which was published in the popular magazines during 2012, considered to be acceptable according to scientific medical information sources. Although in some cases, the amount of evidence is not sufficient. Finally, it could be deduced that the nutrition information published in the Iranian popular magazines are still credible.